A method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry
By introducing hydrophobic modifier and mechanical stirring process into the secondary aluminum ash water-based slurry, combining hydrolysis and high-temperature oxidation reactions, multi-stage porous ceramics are prepared, which solves the problems of environmental pollution and resource waste in secondary aluminum ash treatment. , achieving high porosity and complex structures of ceramic preparation.
Patent Information
- Application Number
- CN202310353194.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-04
AI Technical Summary
The prior art has problems of environmental pollution and resource waste when dealing with secondary aluminum ash, and it is difficult to prepare multi-stage pore ceramics with high porosity and complex structures.
Multi-stage porous ceramics are prepared by introducing a hydrophobic modifier and combining with a mechanical stirring process, using the hydrolysis reaction of the Al-containing active ingredient in the secondary aluminum ash and high-temperature oxidation reaction. The method includes ball milling, water bath heating, mechanical stirring foaming and high-temperature sintering, etc., to form micron-scale macropores and micropore structures.
It has achieved the preparation of lightweight, high-strength, uniform communication pore structures, and is characterized by low cost, simple process and strong controllability. It is suitable for insulation materials, filter materials, catalyst carriers, etc.
Smart Images

Figure CN116444251B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic non-metallic materials, and in particular relates to a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry. Background Art
[0002] Aluminum ash refers to the waste slag produced during the production process of the aluminum industry, and its main components include metal Al, AlN, Al2O3, SiO2, CaO, MgO, etc. With the continuous expansion of the production scale of my country's aluminum industry, the output of aluminum ash has also continued to increase. Aluminum ash is divided into primary aluminum ash and secondary aluminum ash. Secondary aluminum ash is the waste after the extraction of metal aluminum from primary aluminum ash. Its main components include metal aluminum (5-20wt.%), alumina (30-60wt.%), AlN (10-30wt.%) and some salts (5-15wt.%). At present, the treatment of secondary aluminum ash mainly includes storage, landfill and resource utilization, but there are generally a series of environmental problems such as low disposal rate, occupation of land resources, harm to air and groundwater, etc. A green resource utilization method is urgently needed to improve the environment and provide an effective way for new product development.
[0003] At present, the harmlessly treated secondary aluminum ash can be used to prepare cement, ceramics, refractory materials, polyaluminum chloride, foam insulation bricks, ordinary building bricks, artificial stone bricks and other products. Porous ceramics have the characteristics of low bulk density, high specific surface area, low thermal conductivity, high temperature resistance, corrosion resistance, etc., and are widely used in catalytic filtration, biological scaffolds, thermal insulation, lightweight structural components, etc. Macropores have excellent permeability, but they make the material brittle and have low strength. Micropores can increase the specific surface area of the material, making it applicable in the fields of adsorption and catalysis. Multi-level porous ceramics have become the development trend of porous ceramics because they integrate the advantages brought by various pore structures and maximize the functions of the same volume. The current common method requires the secondary aluminum ash to be pre-treated for desalting and denitrification to prevent the hydrolysis reaction of active ingredients such as AlN and Al.
[0004] Chinese patent CN109704722A discloses a method for preparing foam ceramic slurry with aluminum ash, which uses aluminum ash as the main raw material, and by adding auxiliary raw materials, plasticizers, binders, rheological agents, dispersants, etc., the prepared foam ceramic slurry has good stability and thixotropy, is simple and convenient to operate, and the process is environmentally friendly and pollution-free. It is suitable for preparing foam ceramics by organic foam impregnation method, and its molding method is to impregnate the organic foam into the slurry, squeeze and dry it, and finally remove the template at high temperature to obtain ceramics. However, this method focuses on the preparation of bubble-free slurry, and the pore structure of foam ceramics theoretically comes from the organic foam template. There is no embodiment of preparing ceramics, and there is a lack of practical demonstration.
[0005] Chinese patent CN109970456A discloses a method for recycling and reusing aluminum ash residue, which includes rolling and grinding the aluminum ash residue, separating iron impurities and metallic aluminum by magnetic separation, obtaining secondary aluminum ash, washing the secondary aluminum ash with water, adding a certain proportion of kaolin, bentonite and talc to mix to obtain wet grinding slurry, further adding stabilizers and surfactants to prepare slurry, thereby obtaining foam ceramics. However, the pore-forming method of the invention is an organic template method, and complex steps such as washing and defluorination are required, which is costly.
[0006] Chinese patent CN113735611A discloses a method for preparing low-shrinkage porous ceramics by high-temperature self-foaming of aluminum ash slag, which uses secondary aluminum ash slag as the main raw material, spray granulation, dry pressing molding, and high-temperature sintering to finally obtain low-shrinkage porous ceramic materials. The process is simple and easy, eliminating the complicated desalting and denitrogenation process, and using its high-temperature expansion to offset the shrinkage caused by sintering. Its pore-forming method only relies on the oxidation reaction of Al-containing active ingredients at high temperature to produce gas, and the blank is a dry-pressed compact. Compared with this patent, the pore structure obtained by this method is single, the prepared porous ceramics have a higher volume density, and it is difficult to prepare high-porosity products. Its dry pressing molding method requires a relatively simple mold shape, which makes it difficult to prepare complex and delicate blanks. At the same time, unidirectional pressurization makes the pressure distribution uneven, which can easily lead to shrinkage and cracking of the sample.
[0007] Chinese patent CN113563102A discloses a method for preparing porous ceramics by in-situ solidification molding of aluminum ash water-based slurry, which is performed by adding a dispersant, a binder, a sintering aid and water to aluminum ash or a mixture of aluminum ash and ceramic powder, mixing evenly to obtain a solid-liquid mixed phase slurry, and then heating and solidifying, demolding, drying and sintering to obtain porous ceramics. Its pore-forming mechanism is to use the hydrolysis of Al-containing active components to generate gas, and the Al-containing active components generate chemical reactions during high-temperature sintering to generate gas as a pore-forming source. Summary of the invention
[0008] In view of the above technical problems, the present invention provides a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry. The method introduces a hydrophobic modifier, foams through a mechanical stirring process to obtain a micron-level pore structure, further combines the normal temperature hydrolysis process of the Al-containing active component in the secondary aluminum ash to produce an aluminum hydroxide sol to strengthen the green body, and simultaneously generates gas to obtain a pore wall open-pore structure, and further sintering to produce a high-temperature oxidation reaction to obtain a multi-level porous ceramic.
[0009] The technical solution adopted by the present invention is:
[0010] A method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, the method comprising:
[0011] Mixing water, secondary aluminum ash or secondary aluminum ash and ceramic powder and ball milling to obtain a uniformly dispersed slurry;
[0012] The slurry is heated in a water bath, and the Al-containing active components in the secondary aluminum ash are partially hydrolyzed by controlling the temperature and time of the water bath, and after standing for a period of time, a hydrophobic modifier, a binder and a defoamer are added to perform mechanical stirring and foaming;
[0013] The foamed slurry is injected into a mold, demolded to obtain a green body, and then dried and sintered to obtain multi-level porous ceramics.
[0014] Furthermore, during the ball milling and water bath heating, part of the Al-containing active component undergoes a hydrolysis reaction to generate aluminum hydroxide sol and gas;
[0015] The generated aluminum hydroxide sol promotes the formation of stable foam and increases the strength of the green body through gel reaction;
[0016] Micron-sized macropores are obtained by adding the hydrophobic modifier, binder and defoamer and performing foaming in combination with mechanical stirring;
[0017] The generated gas causes micropores to be formed in the green body during the drying process, and the Al-containing active components that are not hydrolyzed during the ball milling and the water bath heating undergo high-temperature oxidation reaction during the sintering process to form micropores.
[0018] The hydrophobic modifier changes the surface property of the unhydrolyzed powder from hydrophilic to partially hydrophobic, so that it can form stable foam. The binder is mainly used to increase the bonding between the powders, thereby enhancing the strength of the blank, and the defoamer is used to eliminate excess foam so that the foam reaches a level that can be molded. Air is introduced by mechanical stirring, and the addition of a binder can encapsulate the gas to form a stable foam, which helps the accompanying room temperature hydrolysis reaction to form an open-cell structure.
[0019] Furthermore, the obtained multi-level porous ceramic has a porosity of 20%-99%, a sintering shrinkage of -10%-10%, and a compressive strength of 0.1-100MPa;
[0020] During the mechanical stirring process, the stirring speed is 1000-2000 rpm and the stirring time is 10-120 min;
[0021] The micron-sized macropores obtained by mechanical stirring and foaming have a pore size of 50-500 μm, and the pore size of the micropores correspondingly generated by hydrolysis gas or high-temperature oxidation reaction is 0.01-50 μm.
[0022] Furthermore, the average particle size of the secondary aluminum ash is 0.1-30 μm;
[0023] The Al-containing active components in the secondary aluminum ash include: one or more of elemental aluminum, aluminum nitride AlN, aluminum carbide Al4C3, and aluminum phosphide AlP.
[0024] In the secondary aluminum ash, the mass percentages of various active components containing Al are: 5-20wt.% of elemental aluminum, 10-30wt.% of aluminum nitride AlN, less than 5wt.% of aluminum carbide Al4C3, and less than 5wt.% of aluminum phosphide AlP;
[0025] Specifically, during the ball milling and water bath heating, the Al-containing active ingredient undergoes a hydrolysis reaction, and the elemental aluminum generates aluminum hydroxide sol and hydrogen, AlN generates aluminum hydroxide sol and ammonia, Al4C3 generates aluminum hydroxide sol and CH4, and AlP generates aluminum hydroxide sol and PH3; the corresponding reaction formula is:
[0026] 2Al(s)+4H2O(l)→2AlOOH(amorphous)+3H2(g);
[0027] AlN(s)+2H2O(l)→AlOOH(amorphous)+NH3(g);
[0028] Al4C3(s)+12H2O(l)→4Al(OH)3(s)+3CH4(g);
[0029] AlP(s)+3H2O(l)→Al(OH)3(s)+PH3(g).
[0030] Furthermore, the solid content in the slurry is 5-80wt.%; the solid in the slurry is secondary aluminum ash or a mixture of secondary aluminum ash and ceramic powder, the secondary aluminum ash accounts for 10-100wt.% of the total mass of the solid in the slurry, and the remainder is ceramic powder.
[0031] Furthermore, the ceramic powder is an inorganic non-metallic material powder, including pure ceramic powder and / or inorganic non-metallic solid waste powder; the pure ceramic powder includes alumina, quartz powder, kaolin, clay, mullite powder, and the inorganic non-metallic solid waste powder includes one or more of fly ash, coal gangue, tailings, metallurgical slag, waste incineration ash or waste glass.
[0032] Furthermore, during the water bath heating process, the water bath temperature is 30-95°C, and the heating time is 5min-48h;
[0033] The standing process is standing at room temperature for 5 minutes to 14 days.
[0034] Further, the hydrophobic modifier is one or more of sodium dodecyl sulfate, cocoamido betaine, fatty acid, oxidized polyethylene, propionic acid, acetic acid, butyric acid, valeric acid, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium α-olefin sulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexylamine, Tween 20, Tween 40, Tween 80, propyl gallate, and octyl gallate, and the addition amount of the hydrophobic modifier accounts for 0.01wt.%-10.00wt.% of the total mass of solids in the slurry;
[0035] Furthermore, the binder is one or more of polyvinyl alcohol, polyvinyl butyral, sodium carboxymethyl cellulose, silica sol, stearic acid, glycerol, polypropylene, and aluminum phosphate (Lithopix P15), and the amount of the binder added accounts for 0.01-10.00wt.% of the total solid mass in the slurry.
[0036] The defoamer is one or more of alkyl polyalkylene glycol ether (Contraspum K 1012), polydimethylsiloxane, ethanol, fatty acid ester, polyether modified silicon, and dimethyl silicone oil. The amount of the defoamer added is 0.01-10.00wt.% of the total solid mass in the slurry.
[0037] Furthermore, during the sintering process, the sintering temperature is 800-1900°C and the heat preservation time is 5min-24h; experiments were conducted by controlling variables to change a single sintering parameter. The experiments showed that if the range is exceeded, such as the sintering temperature is too high or too low, the obtained product will be completely densified or unfired ceramic.
[0038] Beneficial technical effects of the present invention:
[0039] (1) The method provided by the present invention obtains a micron-sized macroporous structure (50-500 μm) by mechanical stirring process combined with a hydrophobic modifier, a binder, and a defoaming agent; then, the gas generated by the hydrolysis process of the Al-containing active ingredient is used to obtain a pore wall open-porous structure (0.01-50 μm micropores), and the pore wall open-porous structure refers to the pore structure of the inner wall of the macropore; further, the sintering is used to generate a high-temperature oxidation reaction to obtain a pore wall mesoporous structure (0.01-50 μm micropores), and the molding method mainly relies on natural drying. Among them, the pore wall mesoporous structure refers to the microporous structure around or on the inner wall of the macropore.
[0040] (2) The method provided by the present invention makes full use of the characteristics of the Al-containing active ingredients in secondary aluminum ash, and utilizes its characteristics of hydrolyzing to generate aluminum hydroxide sol and gas. The generated aluminum hydroxide sol can fix the ceramic particles in the raw material components therein, cover the surface of the ceramic particles, form a gel and thereby increase the strength of the green body; the gas generated during the hydrolysis process can be used to form a pore wall open structure (0.01-50μm micropores) in the green body during the drying process; and finally a multi-level porous ceramic with excellent comprehensive performance is obtained.
[0041] (3) The multi-level porous ceramic product prepared by the method of the present invention has the characteristics of light weight, high strength and uniform interconnected pore structure. The obtained multi-level porous ceramic has excellent comprehensive performance, low cost, simple process, strong controllability, no need for expensive equipment, and easy industrial production. It is expected to be used as thermal insulation material, filter material, catalyst carrier and lightweight structural parts.
[0042] (4) The present invention realizes the resource utilization of hazardous solid waste secondary aluminum ash, and can be synergistically utilized with other silicon-aluminum-based solid wastes, providing a new idea for the recycling of solid wastes, and can synergistically process a variety of solid wastes, which is conducive to the high-value utilization of solid wastes.
[0043] (5) Compared with Chinese patent CN109704722A, the method provided by the present invention controls the temperature and time of the water bath to hydrolyze part of the aluminum-containing active ingredients, and the generated aluminum hydroxide sols can be cross-linked with each other, and further injection molded and dried. During the hydrolysis process and the high-temperature sintering process, the aluminum-containing active ingredients react to form pores.
[0044] (6) Compared with Chinese patent CN113563102A, in the foaming process provided by the present invention, mechanical stirring and foaming are the main sources of the green body pore structure, rather than the hydrolysis of aluminum-containing active ingredients to generate gas. Since the mechanical stirring and foaming, injection molding, and demolding molding processes are relatively short, the pores of the green body obtained by stirring have already been formed, and the room temperature hydrolysis reaction is carried out slowly along with the above stages, which can only play the role of forming an open-pore structure on the green body pore wall, rather than using water bath heating to accelerate hydrolysis to generate pores. The present invention is more suitable for preparing high-porosity, open-pore structure multi-level pore ceramics, and has a shorter production cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The present invention is a flowchart of a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry in an embodiment of the present invention.
[0046] Figure 2 This is a SEM image of the fracture of the green body (green body after drying) obtained in Example 1 of the present invention.
[0047] Figure 3 This is a SEM image of the fracture of the multi-level porous ceramic obtained in Example 1 of the present invention.
[0048] Figure 4 This is the XRD diagram of the multi-level porous ceramic obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0049] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0050] The following is combined with Figure 1-4 The present invention is further described in detail with specific embodiments:
[0051] Example 1
[0052] This embodiment provides a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, such as Figure 1 As shown, the method includes:
[0053] (1) secondary aluminum ash with an average particle size of 5 μm and water are mixed together and ball milled to obtain a uniformly dispersed slurry; the solid content in the slurry is 30 wt.%;
[0054] (2) The ball-milled slurry was heated and hydrolyzed in a water bath at 70°C for 3 h. After the water bath, the slurry was allowed to stand at room temperature for 24 h.
[0055] (3) adding a hydrophobic modifier, cocoamido betaine, a binder, polyvinyl alcohol, and a defoamer, ethanol, to the slurry after standing, and then mechanically stirring with a stirrer;
[0056] The amount of the hydrophobic modifier added is 10.00wt.% of the total mass of the solids in the slurry; the amount of the binder added is 0.05wt.% of the total mass of the solids in the slurry; the amount of the defoamer added is 1.00wt.% of the total mass of the solids in the slurry; the speed of the mechanical stirring is 2000rpm, and the stirring is for 30min;
[0057] (4) The stirred foam slurry is injected into a mold, demolded to obtain a green body, and the green body is allowed to stand and dry to obtain a dry green body. The SEM image of the green body fracture after drying is as follows: Figure 2 As shown;
[0058] (5) The dried green body was sintered at high temperature and kept at 1400° C. for 1 h to obtain a multi-level porous ceramic with uniform pore distribution, whose porosity was 90%, sintering shrinkage was 11.8%, and compressive strength was 10 MPa; the average pore size of the macropores obtained by mechanical stirring and foaming was 150 μm, and the average pore size of the micropores corresponding to the hydrolysis gas or high-temperature oxidation reaction was 25 μm. The SEM image of the fracture of the multi-level porous ceramic in this embodiment is shown in FIG. Figure 3As shown; XRD pattern as Figure 4 shown.
[0059] Example 2
[0060] This embodiment provides a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, the method comprising:
[0061] (1) secondary aluminum ash with an average particle size of 10 μm, aluminum oxide, and water are mixed together and ball-milled to obtain a uniformly dispersed slurry; the solid content in the slurry is 80 wt.%, of which the secondary aluminum ash accounts for 10 wt.% of the total solid mass in the slurry;
[0062] (2) The ball-milled slurry was placed in a water bath for heating and hydrolysis at 90°C for 6 hours. After the water bath, the slurry was allowed to stand at room temperature for 14 days.
[0063] (3) adding valeric acid, a hydrophobic modifier, polyvinyl butyral, a binder, and Contraspum K 1012 to the slurry after standing, and then mechanically stirring with a stirrer;
[0064] The amount of the hydrophobic modifier added is 0.05wt.% of the total mass of the solids in the slurry; the amount of the binder added is 10.00wt.% of the total mass of the solids in the slurry; the amount of the defoamer added is 2wt.% of the total mass of the solids in the slurry; the speed of the mechanical stirring is 1500rpm, and the stirring is for 40min;
[0065] (4) injecting the stirred foam slurry into a mold, demolding to obtain a green body, and leaving the green body to stand and dry to obtain a dried green body;
[0066] (5) The dried green body is sintered at high temperature and kept at 1600° C. for 5 min to obtain a multi-level porous ceramic with uniform pore distribution, a porosity of 50%, a sintering shrinkage of -10%, and a compressive strength of 75 MPa; the average pore size of the macropores obtained by mechanical stirring and foaming is 80 μm, and the average pore size of the micropores corresponding to the hydrolysis gas or high-temperature oxidation reaction is 0.01 μm.
[0067] Example 3
[0068] This embodiment provides a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, the method comprising:
[0069] (1) secondary aluminum ash with an average particle size of 30 μm, coal gangue, and water are mixed together and ball milled to obtain a uniformly dispersed slurry; the solid content in the slurry is 5 wt.%, of which the secondary aluminum ash accounts for 80 wt.% of the total solid mass in the slurry;
[0070] (2) The ball-milled slurry was placed in a water bath for heating and hydrolysis at 95°C for 5 minutes. After the water bath, the slurry was allowed to stand at room temperature for 5 minutes.
[0071] (3) adding a hydrophobic modifier sodium α-olefin sulfonate, a binder silica sol, and a defoaming agent dimethyl silicone oil to the slurry after standing, and then mechanically stirring with a stirrer;
[0072] The amount of the hydrophobic modifier added is 5.00wt.% of the total mass of the solids in the slurry; the amount of the binder added is 0.01wt.% of the total mass of the solids in the slurry; the amount of the defoamer added is 10.00wt.% of the total mass of the solids in the slurry; the speed of the mechanical stirring is 1000rpm, and the stirring is for 10min;
[0073] (4) injecting the stirred foam slurry into a mold, demolding to obtain a green body, and leaving the green body to stand and dry to obtain a dried green body;
[0074] (5) The dried green body is sintered at high temperature and kept at 1200°C for 3 h to obtain a multi-level porous ceramic with uniform pore distribution, a porosity of 60%, a sintering shrinkage of 10%, and a compressive strength of 40 MPa; the average pore size of the macropores obtained by mechanical stirring and foaming is 500 μm, and the average pore size of the micropores corresponding to the hydrolysis gas or high-temperature oxidation reaction is 50 μm.
[0075] Example 4
[0076] This embodiment provides a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, the method comprising:
[0077] (1) secondary aluminum ash with an average particle size of 0.1 μm, waste glass, and water are mixed together and ball-milled to obtain a uniformly dispersed slurry; the solid content in the slurry is 60 wt.%, of which the secondary aluminum ash accounts for 20 wt.% of the total solid mass in the slurry;
[0078] (2) The ball-milled slurry was heated and hydrolyzed in a water bath at 30°C for 48 hours. After the water bath, the slurry was allowed to stand at room temperature for 7 hours.
[0079] (3) adding a hydrophobic modifier, sodium dodecyl sulfate, a binder, Lithopix P15, and a defoaming agent, fatty acid ester to the slurry after standing, and then mechanically stirring with a stirrer;
[0080] The amount of the hydrophobic modifier added is 9.50wt.% of the total mass of the solids in the slurry; the amount of the binder added is 0.05wt.% of the total mass of the solids in the slurry; the amount of the defoamer added is 0.50wt.% of the total mass of the solids in the slurry; the speed of the mechanical stirring is 1600rpm, and the stirring is for 50min;
[0081] (4) injecting the stirred foam slurry into a mold, demolding to obtain a green body, and leaving the green body to stand and dry to obtain a dried green body;
[0082] (5) The dried green body is sintered at high temperature and kept at 800°C for 6 hours to obtain a multi-level porous ceramic with uniform pore distribution, a porosity of 99%, a sintering shrinkage of -6%, and a compressive strength of 0.5 MPa; the average pore size of the macropores obtained by mechanical stirring and foaming is 200 μm, and the average pore size of the micropores produced by hydrolysis gas or high-temperature oxidation reaction is 3 μm.
[0083] Example 5
[0084] This embodiment provides a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, the method comprising:
[0085] (1) secondary aluminum ash with an average particle size of 1 μm, metallurgical slag, and water are mixed together and ball-milled to obtain a uniformly dispersed slurry; the solid content in the slurry is 70 wt.%, of which the secondary aluminum ash accounts for 15 wt.% of the total solid mass in the slurry;
[0086] (2) The ball-milled slurry was heated and hydrolyzed in a water bath at 85°C for 5 hours. After the water bath, the slurry was allowed to stand at room temperature for 10 hours.
[0087] (3) adding a hydrophobic modifier Tween 20, a binder stearic acid and a defoaming agent polyether-modified silicon to the slurry after standing, and then mechanically stirring with a stirrer;
[0088] The amount of the hydrophobic modifier added is 6.50wt.% of the total mass of the solids in the slurry; the amount of the binder added is 8.50wt.% of the total mass of the solids in the slurry; the amount of the defoamer added is 0.01wt.% of the total mass of the solids in the slurry; the speed of the mechanical stirring is 1500rpm, and the stirring is for 120min;
[0089] (4) injecting the stirred foam slurry into a mold, demolding to obtain a green body, and leaving the green body to stand and dry to obtain a dried green body;
[0090] (5) The dried green body is sintered at high temperature and kept at 1900°C for 10 hours to obtain a multi-level porous ceramic with uniform pore distribution, a porosity of 20%, a sintering shrinkage of -8%, and a compressive strength of 100 MPa; the average pore size of the macropores obtained by mechanical stirring and foaming is 50 μm, and the average pore size of the micropores produced by hydrolysis gas or high-temperature oxidation reaction is 0.5 μm.
[0091] Example 6
[0092] This embodiment provides a method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, the method comprising:
[0093] (1) secondary aluminum ash with an average particle size of 2 μm, clay, and water are mixed together and ball-milled to obtain a uniformly dispersed slurry; the solid content in the slurry is 40 wt.%, of which the secondary aluminum ash accounts for 60 wt.% of the total solid mass in the slurry;
[0094] (2) The ball-milled slurry was placed in a water bath for heating and hydrolysis at 40°C for 1 hour. After the water bath, the slurry was allowed to stand at room temperature for 9 days.
[0095] (3) adding hydrophobic modifier propyl gallate, binder glycerol and defoamer polyether-modified polysiloxane to the slurry after standing, and then mechanically stirring with a stirrer;
[0096] The amount of the hydrophobic modifier added is 0.01wt.% of the total mass of the solids in the slurry; the amount of the binder added is 3.00wt.% of the total mass of the solids in the slurry; the amount of the defoamer added is 5.00wt.% of the total mass of the solids in the slurry; the speed of the mechanical stirring is 1400rpm, and the stirring is 65min;
[0097] (4) injecting the stirred foam slurry into a mold, demolding to obtain a green body, and leaving the green body to stand and dry to obtain a dried green body;
[0098] (5) The dried green body is sintered at high temperature and kept at 1300°C for 24 hours to obtain a multi-level porous ceramic with uniform pore distribution, a porosity of 53%, a sintering shrinkage of 3.5%, and a compressive strength of 52 MPa; the average pore size of the macropores obtained by mechanical stirring and foaming is 97 μm, and the average pore size of the micropores produced by hydrolysis gas or high-temperature oxidation reaction is 25 μm.
[0099] The present invention studies the influence of the solid content of the slurry on the product, and sets the content of secondary aluminum ash in the slurry to 20wt.%, 30wt.%, 40wt.%, and 50wt.%, respectively. The other parameters are the same as those in Example 1, and the results are shown in Table 1. As the amount of secondary aluminum ash added increases, the amount of aluminum hydroxide sol generated increases, and the viscosity increases due to the mutual cross-linking of aluminum hydroxide, which reduces the size of the encapsulated pores and thus reduces the size of the macropores. The increase in viscosity reduces the size of the micropores, but as the solid content increases, the amount of aluminum-containing active ingredients increases, and the size of the micropores shows an increasing trend. The sintering line shrinkage and open porosity of the product decrease, and the compressive strength increases.
[0100] Table 1. Effect of different solid content on product performance
[0101]
[0102] The present invention studies the amount of binder added during the stirring process, and sets the binder content to 0.01wt.%, 1.00wt.%, 5wt.%, and 10wt.% of the total mass of the solid in the slurry, respectively. Other parameters are the same as those in Example 1, and the results are shown in Table 2. Since the binder can increase the viscosity of the slurry, the size of the encapsulated bubbles is reduced, and the size of the macropores and micropores formed thereby tends to decrease. The increase in the binder increases the compressive strength of the green body and reduces the sintering line shrinkage.
[0103] Table 2. Effect of different binder contents on product performance
[0104]
[0105] The present invention studies the water bath temperature, and sets the water bath temperature to 30°C, 60°C, and 90°C respectively. The other parameters are the same as those in Example 1, and the results are shown in Table 3 below. As the water bath temperature increases, the hydrolysis of the aluminum-containing active components in the slurry is accelerated, the content of aluminum hydroxide in the slurry increases, the aluminum hydroxide cross-linking effect increases the viscosity, the size of the encapsulated gas decreases, the size of the generated macropores decreases, the remaining aluminum-containing active components decrease, and the micropores tend to decrease. The reduction of the remaining aluminum-containing active components reduces the high-temperature reaction substances, increases the sintering line shrinkage, reduces the open porosity, and increases the compressive strength.
[0106] Table 3. Effect of different water bath temperatures on product performance
[0107]
[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry, characterized in that: The method comprises: Mixing water, secondary aluminum ash or secondary aluminum ash and ceramic powder and ball milling to obtain a uniformly dispersed slurry; The slurry is heated in a water bath, and the Al-containing active components in the secondary aluminum ash are partially hydrolyzed by controlling the temperature and time of the water bath, and after standing for a period of time, a hydrophobic modifier, a binder and a defoamer are added to perform mechanical stirring and foaming; The foamed slurry is injected into a mold, demolded to obtain a green body, and dried and sintered to obtain a multi-level porous ceramic; The Al-containing active components in the secondary aluminum ash include: one or more of elemental aluminum, aluminum nitride AlN, aluminum carbide Al4C3, and aluminum phosphide AlP; the mass percentages of various Al-containing active components in the secondary aluminum ash are: elemental aluminum 5-20wt.%, aluminum nitride AlN 10-30wt.%, aluminum carbide Al4C3 less than 5wt.%, and aluminum phosphide AlP less than 5wt.%; the average particle size of the secondary aluminum ash is 0.1-30μm; The solid content in the slurry is 40-80wt.%; the solid in the slurry is secondary aluminum ash or a mixture of secondary aluminum ash and ceramic powder, the secondary aluminum ash accounts for 10-60wt.% of the total mass of the solid in the slurry, and the remainder is ceramic powder; During the water bath heating process, the water bath temperature is 30-90°C and the heating time is 5min-48h; During the mechanical stirring process, the stirring speed is 1000-2000 rpm and the stirring time is 10-120 min; The binder is one or more of polyvinyl alcohol, polyvinyl butyral, sodium carboxymethyl cellulose, silica sol, stearic acid, glycerol, polypropylene, and aluminum phosphate, and the amount of the binder added accounts for 0.01-3.00wt.% of the total mass of the solid in the slurry; The defoamer is one or more of alkyl polyalkylene glycol ether, polydimethylsiloxane, ethanol, fatty acid ester, polyether modified silicon, and dimethyl silicone oil. The amount of the defoamer added is 0.01-10.00wt.% of the total solid mass in the slurry.
2. The method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry according to claim 1, characterized in that: During the ball milling and water bath heating, part of the Al-containing active component undergoes a hydrolysis reaction to generate aluminum hydroxide sol and gas; The generated aluminum hydroxide sol promotes the formation of stable foam and increases the strength of the green body through gel reaction; Micron-sized macropores are obtained by adding the hydrophobic modifier, binder and defoamer and performing foaming in combination with mechanical stirring; The generated gas causes micropores to be formed in the green body during the drying process, and the Al-containing active components that are not hydrolyzed during the ball milling and the water bath heating undergo high-temperature oxidation reaction during the sintering process to form micropores.
3. The method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry according to claim 2, characterized in that: The prepared multi-level porous ceramic has a porosity of 20%-99%, a sintering shrinkage of -10%-10%, and a compressive strength of 0.1-100MPa.
4. The method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry according to claim 2, characterized in that: The pore size of the micron-sized macropores obtained by mechanical stirring and foaming is 50-500 μm, and the pore size of the micropores generated by the hydrolysis gas or high-temperature oxidation reaction process is 0.01-50 μm.
5. The method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry according to claim 1, characterized in that: The ceramic powder is an inorganic non-metallic material powder, including pure ceramic powder and / or inorganic non-metallic solid waste powder; the pure ceramic powder includes one or more of alumina, quartz powder, kaolin, clay, and mullite powder, and the inorganic non-metallic solid waste powder includes one or more of fly ash, coal gangue, tailings, metallurgical slag, garbage incineration ash or waste glass.
6. The method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry according to claim 1, characterized in that: The standing process is standing at room temperature for 5 minutes to 14 days.
7. The method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry according to claim 1, characterized in that: The hydrophobic modifier is one or more of sodium dodecyl sulfate, cocoamido betaine, fatty acid, oxidized polyethylene, propionic acid, acetic acid, butyric acid, valeric acid, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium α-olefin sulfonate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexylamine, Tween 20, Tween 40, Tween 80, propyl gallate, and octyl gallate, and the added amount of the hydrophobic modifier accounts for 0.01wt.%-10.00wt.% of the total mass of the solids in the slurry.
8. The method for preparing multi-level porous ceramics by foaming secondary aluminum ash water-based slurry according to claim 1, characterized in that: During the sintering process, the sintering temperature is 800-1900° C. and the temperature is kept for 5 minutes to 24 hours.
Citation Information
Patent Citations
Method for preparing foam ceramic slurry from aluminum ash
CN109704722A
Aluminum ash recovering and reutilizing method
CN109970456A
Method for preparing porous ceramic by in-situ curing molding of water-based slurry containing aluminum ash
CN113563102A
Method for preparing low-shrinkage porous ceramic through high-temperature self-foaming of aluminum ash
CN113735611A
Preparation method for aluminium oxide porous ceramic
CN103910520A